Simultaneous heart-kidney transplantation results in respectable long-term outcome but a high rate of early kidney graft loss in high-risk recipients - a European single center analysis - Beetz, Oliver; Thies, Juliane; Weigle, Clara A.; Ius, Fabio; Winkler, Michael; Bara, Christoph; Richter, Nicolas; Klempnauer, Jurgen; Warnecke, Gregor; Haverich, Axel; Avsar, Murat; Grannas, Gerrit (BMC nephrology, 2021)
Background: In spite of renal graft shortage and increasing waiting times for transplant candidates, simultaneous heart and kidney transplantation (HKTx) is an increasingly performed procedure established for patients with combined end-stage cardiac and renal failure. Although data on renal graft outcome in this setting is limited, reports on reduced graft survival in comparison to solitary kidney transplantation (KTx) have led to an ongoing discussion of adequate organ utilization. Methods: This retrospective study was conducted to evaluate prognostic factors and outcomes of 27 patients undergoing HKTx in comparison to a matched cohort of 27 patients undergoing solitary KTx between September 1987 and October 2019 in one of Europe's largest transplant centers. Results: Median follow-up was 100.33 (0.46-362.09) months. Despite lower five-year kidney graft survival (62.6% versus 92.1%; 111.73 versus 183.08 months; p = 0.189), graft function and patient survival (138.90 versus 192.71 months; p = 0.128) were not significantly inferior after HKTx in general. However, in case of prior cardiac surgery requiring sternotomy we observed significantly reduced early graft and patient survival (57.00 and 94.09 months, respectively) when compared to patients undergoing solitary KTx (183.08 and 192.71 months; p < 0.001, respectively) or HKTx without prior cardiac surgery (203.22 and 203.22 months; p = 0.016 and p = 0.019, respectively), most probably explained by the significantly increased rate of primary nonfunction (33.3%) and in-hospital mortality (25.0%). Conclusions: Our data demonstrates the increased rate of early kidney graft loss and thus significantly inferior graft survival in high-risk patients undergoing HKTx. Thus, we advocate for a "kidney-after-heart" program in such patients to ensure responsible and reasonable utilization of scarce resources in times of ongoing organ shortage crisis.
Gesehen am 06.08.2021